2022
DOI: 10.1186/s41984-022-00172-y
|View full text |Cite
|
Sign up to set email alerts
|

High-grade glioma and solitary metastasis: differentiation by spectroscopy and advanced magnetic resonance techniques

Abstract: Background The differentiation by means of magnetic resonance between high-grade gliomas and intracranial solitary single metastasis is of the utmost importance since they condition both surgical and complementary treatment. Results Retrospective study that analyzes the parameters of advanced magnetic resonance imaging: spectroscopy, diffusion and perfusion, specifically focused on the differences in the coefficients of the metabolites Cho/Cr, Cho/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…We simultaneously calculated the average value of the ratio of Cho to Cr in the tumor region (tCho/Cre) and peritumor area (pCho/Cre) of the GBM group and the SBM group; the results showed that the GBM group had higher tCho/Cre and pCho/Cre ratios than the SBM group. This result is similar to the findings of Arévalo-Sáenz [ 28 ] and Server et al . [ 29 ]…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We simultaneously calculated the average value of the ratio of Cho to Cr in the tumor region (tCho/Cre) and peritumor area (pCho/Cre) of the GBM group and the SBM group; the results showed that the GBM group had higher tCho/Cre and pCho/Cre ratios than the SBM group. This result is similar to the findings of Arévalo-Sáenz [ 28 ] and Server et al . [ 29 ]…”
Section: Discussionsupporting
confidence: 93%
“…The cutoff of 1.115 for pCho/NAA in Arévalo-Sáenz’s study had higher sensitivity and specificity (93.87% and 93.33%, respectively). [ 28 ] In addition, the pCho/NAA cutoff of 1.10 in Tsougos et al .’s study had lower sensitivity (78%) but higher specificity (93%) than that in our study. [ 26 ]…”
Section: Discussionmentioning
confidence: 99%